Spin Wave Modes of Two Magnetostatic Coupled Spin Transfer Torque Nano-Oscillators - Altbir-Drullinsky, D; Allende-Prieto, S; Escobar-Donoso, R; Mancilla-Almonacid, D (American Institute of Physics, 2018)
A detailed analytical and numerical study of the spin wave modes of two nanopillar spin torque nano-oscillators coupled by magnetostatic interactions is presented under the macrospin approximation. Results show that the normal modes of the system oscillate with the magnetizations in-phase or anti-phase in both disks. The frequencies and critical current densities necessary to induce auto-oscillations of the spin wave modes of the coupled system depend on the relative position of the nanopillars and the applied magnetic field. If the oscillators are identical, these modes are degenerate at a certain relative position of the nanopillars, while if the oscillators are non-identical, such degeneracy is removed. Then, we can conclude that the magnetostatic coupling between two spin transfer torque nano-oscillators is a powerful mechanism to control the spin wave modes of these systems. © 2018 Author(s).